An Analysis of Factors Influencing English Education Department Students’ Vocabulary Size - Astri Agustin*; Valentina Dyah Arum Sari (Universitas Syiah Kuala, 2023)
This study aimed to assess the vocabulary size of undergraduate students and identify the factors that influenced it. The research involved 15 students from different semesters within the English Education Department at a Private University in Yogyakarta. The study applied mixed-method approach. Questionnaires and Interview were used for gathering the data. The researchers used Vocabulary Size Test that developed by Nation and Beglar (2007). The findings indicated that 13 students had a vocabulary size of 5,000–6,000 word families. Regarding the factors affecting the students’ results, it was revealed that external factors had a more significant influence with a result of 60.5% and a gap of 3% with internal factors, which is 57.5%.